Is this correct: Solve: (x+5)^2 = 3 I get: x = -5 (+/-) sqrt (3) Problem #2 Solve: 5(x-2)^2 = 3 I get: x = 3 (+/-) ((sqrt(3))/(5) No on the second. YOu have take the sqrt5 slso, so x= 2+- sqrt(3/5) correct on the first.
Factor the polynomial P(x)=x^3-2x^2-13x-10. Then solve the equation P(x)=0. This is what I got: P(x)=(x+1)(x^2-3x-10) P(x)=(x+1)(x-5)(x+2) When it says solve the equation P(x)=0 does it means solve for x?
If I had a math problem 2x^4 x y^-4 x z^-3 / 3x^2 x y^-3 x z^4. In simpler terms it would look like this: 2x^4 X y^-4 X z^-3 ------------------- 3x^2 X y^-3 X z^4 When I tried to solve this I got 6x^2 X y^-1 X 2^-7. Am I correct?